2017
DOI: 10.1007/s11356-017-0431-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of element composition and extraterrestrial material occurrence in moss and lichen samples from King George Island (Antarctica) using reactor neutron activation analysis and SEM microscopy

Abstract: Seven lichens (Usnea antarctica and U. aurantiacoatra) and nine moss samples (Sanionia uncinata) collected in King George Island were analyzed using instrumental neutron activation analysis, and concentration of major and trace elements was calculated. For some elements, the concentrations observed in moss samples were higher than corresponding values reported from other sites in the Antarctica, but in the lichens, these were in the same range of concentrations. Scanning electron microscopy (SEM) and statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…The content of Ti at most of our sites is also comparable to the range of background concentrations known worldwide for this element (e.g. Cecconi et al., 2018 ; Bargagli et al., 2002 ; Mróz et al., 2018 ; Bubash et al., 2020 ; Takala and Olkkonen, 1985 ; Darnajoux et al., 2015 ). In a highly polluted site, Bačkor & Fahselt (2004) reported high levels of Ti (169 μg/g) for Cladonia pleurota near the abandoned O'Donnell roast bed near Sudbury, ON, but lower values 19.9 and 32.5 μg/g for lichens in the control site and in recolonized forest.…”
Section: Discussionsupporting
confidence: 82%
“…The content of Ti at most of our sites is also comparable to the range of background concentrations known worldwide for this element (e.g. Cecconi et al., 2018 ; Bargagli et al., 2002 ; Mróz et al., 2018 ; Bubash et al., 2020 ; Takala and Olkkonen, 1985 ; Darnajoux et al., 2015 ). In a highly polluted site, Bačkor & Fahselt (2004) reported high levels of Ti (169 μg/g) for Cladonia pleurota near the abandoned O'Donnell roast bed near Sudbury, ON, but lower values 19.9 and 32.5 μg/g for lichens in the control site and in recolonized forest.…”
Section: Discussionsupporting
confidence: 82%
“…The INAA technique has been used widely to study the elemental composition of samples from Antarctica (e.g. Mróz et al 2018), whether they are sediments, lichens or mosses.…”
Section: Analytical Techniques and Methodsmentioning
confidence: 99%
“…Moreover, there are different studies describing a metal avoidance mechanism, where binding of the metal ion to the cell wall reduces the amount of metals entering the protoplasm of mosses [ 66 , 86 , 87 ]. The cell wall system of mosses seems to be, in fact, an efficient barrier to metals, and particularly Cd, not only in gametophytes but also in sporophytes, in which a higher metal adsorption at cell wall level has been measured [ 78 , 88 , 89 ]. In addition, Basile et al [ 90 , 91 ] observed that metal ions were sequestered inside the placenta of the moss Funaria hygrometrica by cell wall labyrinths, preserving the above sporophyte from being damaged by the metals.…”
Section: Response To Cadmium Toxicity In Charophytes and Bryophytesmentioning
confidence: 99%